The Aggregate Impact of Trade and Migration on Economic Growth and its Components: Evidence from Emerging Economies - Shah, Mohsin; Khan, Hamad Hasul (Asian Development Policy Review, 2020)
The study examines the combined effects as well as separate effects of trade openness and net migration on economic growth and the components of economic growth viz capital-labor ratio, total factor productivity, and labor employment ratio over the period 1960-2017 for the selected emerging economies. The study used two-stage least squares (2SLS) technique. The results reveal that trade openness positively related to economic growth while net migration is negatively related to economic growth. Moreover, the study discovered that trade openness positively impacts capital-labor ratio and total factor productivity and it is negatively related to labor employment ratio whereas net migration is negatively associated with capital-labor ratio, total factor productivity, and positively related to employment ratio. Overall, the study concludes that the flow of migrants hurts economic growth while trade openness aids economic growth in emerging economies. The findings may provide a better understanding and some guidance on policies about trade openness, net migration, and economic growth.